Teatro brasileiro e censura no governo Bolsonaro - Gabriela Lirio (IdeAs)
I aim to investigate the contemporary Brazilian theater scenario in the 21st century following the political changes in the country, especially after the coup of 2016 that ousted President Dilma Rousseff. Starting from the hypothesis that the second decade of the millennium has enhanced the scenic creation of auto-fictional and/or documentary plays, whose themes dealt with the relations between memory and politics in an attempt to confront and denounce the censorship, the lack of funding, and the genocidal policy of the current government. The only country in Latin America to grant amnesty to torturers after the military coup (1964-1984), Brazil finds itself in a threshold situation where human rights and freedom has been constantly under threat. In this sense, theater offers a historical revisitation of themes related to the military dictatorship, the suppression of rights, and of race and gender issues, which will be analyzed in works by authors such as Grace Passô, Renata Carvalho, and Pedro Kosovski.